The civil service under one country, two systems: the cases of Hong Kong and the People's Republic of China - Chan, Hon S. (2003)
Under the principle of "one country, two systems", Hong Kong's and China's civil services are changing, but they clearly are not converging. The civil service reforms made in Hong Kong and China appear to be heading toward two logical extremes: one foward stgrengthening political authority over the civil service, and the other instituting greater institutionalization. What appears to be a problem in Hong Kong may be seen as a solution in China. Not only reform problems, but also reform options, are defined in relation to wider political institutions and changing socioeconomic dynamics. The study shows that while some things do need to be uniform, such as loyalty to the state and central government, a great deal of flexibility regarding administrative systems within one country is possible. There can be a modern nation without a truly national civil service. - Reproduced.
Keywords: Civil service - Hong Kong; Civil service - China; Civil service